Research Progress of Fuzheng Jiedu Huayu Method in Reducing Toxicity and Enhancing Efficacy of Immunotherapy - Yufan CHEN; Sicong LI; Yiyuan CUI; Li FENG (Zhongliu Fangzhi Yanjiu)
Immunotherapy, including immune checkpoint inhibitors, tumor vaccine therapy, oncolytic virotherapy, and adoptive cell therapy, has made remarkably breakthroughs in the field of oncology. Immune checkpoint inhibitors, which block programmed death receptor 1 or programmed death ligand 1, have been included in the first-line clinical treatment for advanced solid tumors, such as non-small cell lung cancer and malignant melanoma. However, primary or secondary drug resistance in tumors severely limits the survival benefits for patients. Immune-related adverse reactions, such as pneumonia, hypothyroidism, hypophysitis, and myocarditis, also greatly affect the quality of life of patients. Fuzheng Jiedu Huayu is an important concept guiding the prevention and treatment of tumors with traditional Chinese medicine (TCM). It is also a curative principle and therapeutic TCM method to reduce the toxicity and enhance the efficacy of immunotherapy. This article summarizes the research progress of immunotherapy and discusses how TCM reduces the toxicity and enhances the efficacy of immunotherapy, hoping to provide a reference for the integrated treatment of tumors with TCM and immunotherapy.